2007
DOI: 10.1063/1.2747659
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of a symmetrically confined cylindrical particle in a “Stokes-type” regime

Abstract: To contribute to the study of the influence of the hydrodynamic interactions governing the dynamics of solid particles such as fibers in nondilute regimes, we consider in this work a cylindrical particle confined between two parallel walls at low Reynolds numbers. The particle moves with its axis always parallel to both walls. Our numerical results, derived with a projection method and a finite-volume approach, turn out to be very accurate and enable us to solve different problems using the matrix resistance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…We then consider the case of a circular particle falling in a bounded fluid domain between two vertical walls and then review several of the most commonly-used formulas for the "wall-correction factors" that have been obtained from either fitting to experimental data or using approximate analytical techniques. A fairly extensive overview of settling for cylindrical particles, including many of the wall correction formulas reported in the literature, is given by Champmartin and Ambari [11].…”
Section: Approximate Formulas For Settling Velocitymentioning
confidence: 99%
“…We then consider the case of a circular particle falling in a bounded fluid domain between two vertical walls and then review several of the most commonly-used formulas for the "wall-correction factors" that have been obtained from either fitting to experimental data or using approximate analytical techniques. A fairly extensive overview of settling for cylindrical particles, including many of the wall correction formulas reported in the literature, is given by Champmartin and Ambari [11].…”
Section: Approximate Formulas For Settling Velocitymentioning
confidence: 99%
“…This is due to the increase of the screen length for Newtonian and dilatant fluids. When the problem is confined geometrically, we showed that the drag force is not anymore zero due to the existence of the Stokes-type solution as established in the Newtonian case [2]. Otherwise, once the solution for the unbounded medium is established, we give a solution for the confined medium numerically and asymptotically.…”
Section: Resultsmentioning
confidence: 85%
“…1). If this cylindrical particle is very long and highly confined, it has been established that the end effects are negligible [2,22]. For pseudoplastic fluids, for which the Stokes' type solution exists, we study the influence of the fluidity ðnÞ and the backflow on the settling velocity.…”
Section: Effect Of the Backflow On The Particle Settling Velocity Formentioning
confidence: 99%
See 1 more Smart Citation
“…The Faxen formula yields reasonably accurate results up to R=L 0.5 [26]. CDFEM is used to solve the settling disk problem similarly to [10], setting gravity g D 1.0, fluid viscosity D 1.0, and the density of the solid s D 1.0.…”
Section: Particle Falling In Viscous Fluidmentioning
confidence: 99%